Urogymnus acanthobothrium sp. nov., a new euryhaline whipray (Myliobatiformes: Dasyatidae) from Australia and Papua New Guinea - Last, Peter R.; White, William T.; Kyne, Peter M. (Zootaxa, 2016)
The Mumburarr Whipray, Urogymnus acanthobothrium sp. nov. is described from a single specimen taken from the Cambridge Gulf, Western Australia, and from images of 10 other specimens from northern Australia and Papua New Guinea (all observed but not collected). It is a very large ray that attains at least 161 cm disc width, making it amongst the largest of the whiprays. The ventral tail below the caudal sting has a low, short-based fold. A ventral tail fold (or a dorsal fold) has not been recorded for any other himanturin stingray in the Indo-West Pacific. Molecular data suggest it is most closely related to a similar but more widely distributed cognate, U. granulatus. Both of these species share a suboval disc shape, similar squamation patterns, and the tail posterior to the sting is entirely white (at least in small individuals). U. acanthobothrium sp. nov. differs from U. granulatus in having a longer and more angular snout, longer tail, more posteriorly inserted caudal sting, lacks white flecks on the dorsal surface, and the ventral disc is uniformly white (rather than white with a broad black margin). It co-occurs with two other morphologically distinct Urogymnus in the region (U. asperrimus and U. dalyensis). Like U. dalyensis it occurs in both brackish and marine waters. A key is proved to the members of the genus Urogymnus.